The mediating effect of attitude on perception towards impact change after watching Islamic films - Wok, Saodah; Abdul Manaf, Nor Faridah; Ismail, Rizalawati (Academic Star Publishing, 2014)
Religious films play an import role in educating the viewers, especially the youth. This study tries to explore the relationships between perception and attitude towards impact change after watching Islamic films. Specifically, it analyses the mediating effect of attitude towards Islamic films for perception on impact change on youth behavior after watching Islamic film. The results of the quasi-experimental design using questionnaire as the research instrument revealed that there are positive relationships between impact change with perception and attitude. Attitude in turn mediates the relationship between perception and impact change. Therefore, the social learning theory tested for the study holds true and the hypotheses developed were supported. In sum, based on the 141 youth studied, Islamic film, as a whole, is able to have a positive impact on them. Therefore, filmmakers, in general, and religious-based filmmakers, in particular, should take heed in producing films with positive issues toward nurturing youth in making youth to possess morally and ethically sound behavior for peace and harmony of the community and the nation.